Features of Thrombi and Diagnostic Accuracy of Impedance Plethysmography in Symptomatic and Asymptomatic Deep Vein Thrombosis - Agnelli, Giancarlo; Cosmi, Benilde; Radicchia, Stefano; Veschi, Franca; Boschetti, Enrico; Lupattelli, Luciano; Rinonapoli, Emanuele; Nenci, Giuseppe G (Thrombosis and Haemostasis, 1993)
Impedance plethysmography (IPG) has high sensitivity and specificity in patients with symptomatic deep vein thrombosis (DVT) while it fails to detect asymptomatic DVT. The aim of this study was to determine whether the features of thrombi such as location, size and occlusiveness could explain the different accuracy of IPG in symptomatic and asymptomatic DVT patients. One-hundred and seventeen consecutive outpatients with a clinical suspicion of DVT and 246 consecutive patients undergoing hip surgery were admitted to the study. In symptomatic patients IPG was performed on the day of referral, followed by venography, while in asymptomatic patients IPG was performed as a surveillance programme, followed by bilateral venography.A venography proved DVT was observed in 37% of the symptomatic patients and 34% of the asymptomatic limbs. A significantly higher proportion of proximal DVTs was found in symptomatic patients than in asymptomatic patients (78% vs 46%; p = 0.001). The mean Marder score, taken as an index of thrombus size, was significantly higher in symptomatic patients than in asymptomatic patients (19.0 vs 9.6; p = 0.0001). A significantly higher proportion of occlusive DVTs was observed in symptomatic than in asymptomatic patients (69% vs 36%; p = 0.001).We conclude that the unsatisfactory diagnostic accuracy of IPG in asymptomatic DVT is due to the high prevalence of distal, small and non occlusive thrombi. Such thrombi are unlikely to cause a critical obstruction of the venous outflow and therefore to produce a positive IPG.